Substance Abuse Disorders in the Parents of ADHD Children, and Parents of Normal Children - Ahmad Alipour (Acta Medica Iranica, 2012)
The objective of the study was to compare the attention-deficit/ hyperactivity, and substance abuse disorders background in the parents of children with attention-deficit/ hyperactivity disorder (ADHD), and the parents of normal children. The available sampling method was used to choose 400 parents of children (200 parents of children with ADHD and 200 parents of normal children), the ages of children were 6-18 years old. The data were collected through the Schedule for Affective Disorders and Schizophrenia (SADS) for parents and the Kiddy Schedule for Affective Disorders and Schizophrenia for School-Age Children-Present and Lifetime version (K-SADS-PL), Connors Adult ADHD Rating Scale (CAARS) and the Wender Utah Rating Scale (WURS) for adult ADHD. The results were analyzed by using SPSS-17 software, based on two-variable Chi-Square and t-tests.and P value in all disorders were equals to P<0.05. The results indicated that substance abuse in parents of children with ADHD is 21% more prevalent, and parents of children with ADHD compared to parents of normal children have 2% ADHD, 9% attention deficit disorder, and 1% hyperactivity disorder more in their background. Therefore, we conclude that there exists a significant difference between the above mentioned disorders in the parents of children with ADHD, and parents of normal children. The high prevalence rate of disorders and background of ADHD in families of individuals with ADHD shows the probability of effect of inheritance in the disorder. Also, it shows that parents of children with ADHD have more substance abuse and history of ADHD in their background.